Trade facilitation: The role of a WTO agreement - Joseph M. Finger (European Centre for International Political Economy (ECIPE), 2008)
The trade facilitation negotiations have been one of the more active topics in the Doha negotiations. At the same time, extensive reforms have been put in place among WTO members, including a number of developing Members. This paper focuses on how a WTO agreement might support the process of reform and capacity-building in developing countries. A number of proposals for improved performance have been tabled, as well as how to ensure that sufficient assistance is provided to enable developing Members to meet the new performance standards. This paper reviews and evaluates the various proposals. Overall, experience provides a sound knowledge basis for international co-operation on trade facilitation, with basic reforms within the capacities of even the poorest countries. However, while a WTO agreement could be a useful guide to productive reforms in developing countries, the mechanics for an extended WTO role in the management of assistance - particularly in making provision of that assistance a WTO obligation of developed countries - would be problematic. To superpose a process that presents the issue as a mercantilist bargain of assistance in exchange for trade reform "concessions" would be to introduce conflict into a relationship that is already productively propelled by a perception of mutual benefit. A possible alternative could be to consider a plurilateral agreement under the WTO umbrella.
Keywords: F13; F15; O19; O24; 330; Trade policy; World Trade Organization; trade facilitation